Accountability and legitimacy dynamics in an Islamic boarding school - Buanaputra, Vogy Gautama (Emerland, 2022)
Purpose – This study aims to investigate the dynamics of legitimacy and accountability relationships in an Indonesian boarding school. It examines how the key actors improve and use accountability mechanisms in the school and how these practices contribute to the organisation’s legitimacy. Design/methodology/approach – This paper uses a qualitative case study approach in an Indonesian boarding school and draws on Black’s (2008) notion of legitimacy and accountability relationships. The qualitative data were collected through face-to-face interviews, observations and documentary analysis. Findings – Accountability mechanisms at Pondok Pesantren Wali Songo (an Islamic boarding school) were developed to alter the habit of conducting organisational affairs based merely on trust between the organisation members without any particular accountability mechanism, a common practice in Indonesian boarding schools. The mechanisms were believed to improve the public trust and bring convenience to the management of the school on the legitimacy (halal) of their doings, which in turn maintain their legitimacy as a provider of Islamic education services. Originality/value – This study highlights the importance of accountability mechanisms in faith-based institutions context to maintain their legitimacy. It provides evidence of the mutual nature of accountability and legitimacy, which is often seen as contrasting concepts by previous studies, by drawing on Black’s (2008) legitimacy and accountability relationships.